Evaluation of the relationship between MARCO and CD36 single-nucleotide polymorphisms and susceptibility to pulmonary tuberculosis in a Chinese Han population - Lao, Wenting (BMC Infect Dis, 2017)
BACKGROUND: Gene polymorphisms impact greatly on a person’s susceptibility to pulmonary tuberculosis (PTB). Macrophage receptor with collagenous structure (MARCO) and CD36 are two scavenger receptors (SRs) that can recognize Mycobacterium tuberculosis (Mtb) and play a key role in tuberculosis infection. Gene polymorphisms of MARCO and CD36 may contribute to tuberculosis risk. METHODS: To investigate whether genetic polymorphisms of MARCO and CD36 are associated with susceptibility to PTB, genomic DNA samples from patients (n = 202) and healthy controls (n = 216) were collected and analyzed by polymerase chain reaction with high-resolution melting analysis. RESULTS: We studied two single nucleotide polymorphisms (SNPs) in MARCO (rs12998782 and rs17009726) and three SNPs in CD36 (rs1194182, rs3211956 and rs10499859). Rs12998782 (P = 0.018) might be associated with susceptibility to PTB. Rs1194182 (P < 0.01) and rs10499859 (P < 0.001) might be associated with resistance to PTB. Rs17009726 and rs3211956 were not associated with susceptibility/resistance to PTB. CONCLUSIONS: These data showed that MARCO rs12998782 may increase PTB risk while two SNPs of CD36, rs1194182 and rs10499859 may reduce the risk, indicating MARCO and CD36 as important receptors in response to PTB. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-017-2595-2) contains supplementary material, which is available to authorized users.